Estimasi Presentase Attributable Risk Pada Populasi (PAR%) Dan Fraksi Etiologis (EF) Faktor Risiko MDR-TB Di RSUD Kota Makassar - Alief Ihram Fatany; Andi Nursiah; Idris (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Tuberculosis (TB) remains a global health problem with 10.7 million new cases and 1.23 million deaths in 2024, further compounded by the emergence of multidrug-resistant tuberculosis (MDR-TB). Existing analyses of MDR-TB risk factors remain limited to the Odds Ratio (OR), which is unable to quantify the magnitude of risk factor contributions at the population level. This study aimed to estimate the Population Attributable Risk Percent (PAR%) and Etiologic Fraction (EF) of risk factors for MDR-TB incidence at Makassar City Regional General Hospital (RSUD Kota Makassar) in 2024. This study is a secondary data analysis based on a publication by Janna et al. (2025), with a sample of 111 TB patients (37 MDR-TB cases and 74 non-MDR-TB controls). PAR% was calculated using Levin's formula [Pₑ(OR−1) / Pₑ(OR−1)+1] × 100% and EF using the formula [(OR−1)/OR] × 100%, focusing on variables that were statistically significant (p < 0.05) with OR > 1. Of the seven variables analyzed, three were statistically significant, namely, side effects of anti-tuberculosis drugs (ATD) with PAR% 93.8% and EF 97.6%; history of previous TB treatment with PAR% 66.3% and EF 90.1%; and undernutritional status (BMI < 18.5 kg/m²) with PAR% 38.2% and EF 61.5%. Management of ATD side effects represents the primary intervention priority, with the potential to prevent 93.8% of MDR-TB cases at RSUD Kota Makassar.